Meningkatkan Nasionalisme Indonesia: Menggali Kepulauan dan Ketahanan Nasional (Perspektif Filsafat Sosial) - Ranubaya, Fransesco Agnes; Hexanno, Sirilus Anantha Deva; Rangga, Werenfridus Kalistus; Endi, Yohanes (Undiksha, 2024)
This research delves into the endeavor to fortify Indonesian nationalism through an exploration of the Archipelago Concept and National Resilience, employing a social philosophy approach. The central inquiry revolves around the role that an understanding of these concepts plays in bolstering nationalism in Indonesia. The primary objective is to assess the impact of comprehending the Archipelago Concept and National Resilience on the level of nationalism in Indonesia, while also scrutinizing the role of social philosophy in interpreting the relationship between these concepts and nationalism. Employing a qualitative analysis with a literature study approach, this research explores relevant literature on the Archipelago Concept, National Resilience, and nationalism, utilizing a social philosophy lens to dissect these concepts in the Indonesian context. Findings reveal that a profound understanding of the Archipelago Concept strengthens Indonesia's national identity by emphasizing unity in cultural, geographic, and ethnic diversity. Simultaneously, National Resilience plays a crucial role in fostering love for the homeland through the preservation of sovereignty, security, and welfare. Within the realm of social philosophy, the research demonstrates that the comprehension of both concepts can be reinforced through reflection and critical thinking about their underlying values. Social philosophy aids in formulating the meaning and relevance of these concepts within the Indonesian social and cultural milieu. In conclusion, this research posits that a deep understanding of Wawasan Nusantara and National Resilience positively reinforces Indonesian nationalism, serving as the bedrock for constructing a robust and inclusive national identity capable of navigating global challenges while upholding unity in diversity